The librarian who measured the earth - Lasky, Kathryn; Hawkes, Kevin (Boston : Little, Brown, 1994)
Describes the life and work of Eratosthenes, the Greek geographer and astronomer who accurately measured the circumference of the Earth.
Includes bibliographical references (p. 48).
Elem. School Library Collection
School Library Journal starred
Wilson's Children
5.7
3-6
Keywords: Eratosthenes -- Juvenile literature; Eratosthenes; Eratosthenes; Astronomers -- Greece -- Biography -- Juvenile literature; Astronomy, Greek -- Juvenile literature; Geographers -- Greece -- Biography -- Juvenile literature; Geography, Ancient -- Juvenile literature; Geographers; Geographers -- Biography; Earth -- Figure -- Measurement -- Juvenile literature; Earth; Earth